2021
DOI: 10.1002/ptr.7219
|View full text |Cite
|
Sign up to set email alerts
|

Potential protective effects of Aloe vera gel on cardiovascular diseases: A mini‐review

Abstract: Cardiovascular diseases (CVDs) comprise the most prevalent causes of morbidity and mortality in both men and women worldwide. CVDs are associated with several risk factors such as hyperlipidemia, diabetes mellitus, hypertension, obesity, tobacco smoking and an unhealthy diet. Currently, in addition to the use of related pharmacological treatments in the management of CVDs, the investigation of other suitable healthcare approaches for these disorders such as the identification of herbal medicines has been consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 72 publications
(154 reference statements)
0
6
0
Order By: Relevance
“…Previous studies have shown that AVG is safe to use (Sabbaghzadegan et al, 2021; Sehgal et al, 2013; Staff, 2011; Vogler & Ernst, 1999). In this study, AVG was well tolerated among HF patients.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Previous studies have shown that AVG is safe to use (Sabbaghzadegan et al, 2021; Sehgal et al, 2013; Staff, 2011; Vogler & Ernst, 1999). In this study, AVG was well tolerated among HF patients.…”
Section: Discussionmentioning
confidence: 96%
“…Some properties of AVG, including antioxidant, anti‐inflammatory, anti‐fibrotic, anti‐hypertensive and antiatherosclerotic activities, can possess direct cardioprotective effects. It can also indirectly show cardiobeneficial effects, by influencing some risk factors such as diabetes mellitus (DM), and hyperlipidemia (Jain et al, 2010; Kumar et al, 2007; Sabbaghzadegan et al, 2021; Sumi et al, 2019; Yang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is because amine vitamins detected in Aloe species are among the water-soluble vitamins that are required for performing specific cellular functions, such as being precursors for coenzymes in the enzymes of intermediary metabolism (Alamgir, 2018). Table 6 summarizes the deficiency of amine vitamins (Kraemer et al, 2012;Griffiths, 2020;Taguchi, 2023) and treated diseases due to the presence of these vitamins, which have various biological effects (Channa et al, 2014;Akaberi et al, 2016;Belayneh et al, 2020;Ahluwalia et al, 2021;Sabbaghzadegan et al, 2021;Taqui et al, 2022). Specific mammalian body systems treated by therapeutic activities Aloe species.…”
Section: Nutraceutical Applicationsmentioning
confidence: 99%